Feeding Habits and Diet of Torquigener flavimaculosus (Hardy & Randall in 1983) along the Tobruk Coast in the Mediterranean Sea, Eastern Libya - Ayiman Bouhuweesh; Abdallah Belhassan; Ayiman Bilhassan (AlQalam Journal of Medical and Applied Sciences, 2025)
This study looked at the eating habits of 161 Torquigener flavimaculosus fish (from the Tetraodontidae family) living along the Tobruk Mediterranean coast. The research was done every month from January to December 2022. It focused on what the fish ate throughout the year, how their diet changed each month, how their diet varied with their size, and how much they ate. T. flavimaculosus eats many types of prey, including Polychaete worms (47.9%), snails (Gastropoda) (17.5%), clams (Bivalvia) (16.4%), Crustaceans (4.9%), sea urchins and starfish (Echinodermata) (4.2%), fish (3.4%), and other foods (5.7%). Polychaete worms, snails, and clams were eaten all year and by all size groups of T. flavimaculosus. The study found that as the fish grew bigger, they ate more polychaete worms, snails, and clams, but less crustaceans and sea urchins. Fish item appeared in the diet of T. flavimaculosus when they reached 13.5-14.4 cm in size (2.1%), and other food items were found in fish measuring 12.5 to 14.4 cm (0.7% to 3.6% repectivey). The fish T. flavimaculosus was very active in eating during spring (67.2%) and autumn (82.4%). However, they ate much less in winter (36.1%) and summer (44.5%). تمت دراسة العادات الغذائية لـ 161 عينة من سمكة أبو نفاخ الصفراء ، التي تسكن ساحل البحر الأبيض المتوسط ​​في طبرق، شهريًا في الفترة من يناير إلى ديسمبر 2022. تم دراسة النظام الغذائي السنوي، والتغيرات الشهرية في تكوين النظام الغذائي، وتنوع النظام الغذائي وتمت دراسة شدة التغذية. وقد وجد ان سمكة أبو نفاخ الصفراء تتغذى على مجموعة واسعة من أنواع الفرائس: الديدان عديدة الاشواك بنسبة (47.9%)، مكمل بأحادية المصراع (17.5%)، ثنائية المصراع 16.4)%)، القشريات (4.9%)، الجلد شوكيات (4.2%)، الاسماك (3.4%) وغيرها من طعام مهضوم او فرائس غير معرفه لتهالك انسجتها بنسبة ( 5.7). وقد تم العثور على الديدان متعددة الأشواك واحادية المصراع وثنائية المصراع على مدار السنة وفي جميع المجموعات الطولية لسمكة أبو نفاخ الصفراء. في الدراسة الحالية، زادت التغذيه على الديدان عديدة الاشواك وأحادية وثنائية المصراع مع زيادة اطوال السمكه بينما تقل القشريات والجلدشوكيات مع زيادة حجم الأسماك. وكانت أنشطة التغذية عالية خلال فصل الربيع (67.2%) وعالية جدا خلال موسم الخريف (82.4%) لسمكة أبو نفاخ الصفراء وكانت أنشطة التغذية ضعيفه جدًا خلال الشتاء (36.1%) والصيف (44.5%) والخريف